Magneto-responsive structural build-up of highly flowable cementitious paste in the presence of PCE superplasticizer. (11th April 2022) - Jiao, Dengwu; Shi, Caijun; De Schutter, Geert
Highlights: Magneto-responsive rheology of highly flowable cement paste with PCE is studied. Flowable cement paste with magnetic particles and PCE can exhibit MR response. PCE increases relative MR effect while slightly decreases absolute MR effect. Applying magnetic field plays a major role in stiffness for cement paste with PCE. Abstract: Magneto-rheology control, by means of adding magnetizable particles and applying magnetic field, is a potential approach to satisfy the contradicting requirements of fresh properties in different casting processes. Polycarboxylate ether (PCE) superplasticizer is an essential component of modern cement-based materials, which significantly affects the viscoelastic properties of cementitious suspensions, and hence the movement and distribution of magnetic particles after applying an external magnetic field. This present research focuses on the following two aspects: whether highly flowable cementitious paste containing both magnetic particles and PCE shows rheological response to an external magnetic field, and if yes, is there a difference of magneto-responsive structural evolution of cementitious pastes with and without PCE? For these purposes, the magneto-responsive structural build-up of highly flowable cementitious pastes with various magnetic particles (two nano-Fe3 O4 particles and one magnetic fly ash) in the presence of PCE, described by the evolution of storage modulus over time, is evaluated. Experimental results show that highly flowable cementitious pastes containing both magnetic particles and PCE indeed exhibit obvious magneto-rheological (MR) responses. The incorporation of PCE significantly increases the relative MR effect while slightly decreases the absolute MR effect. By comparing the magneto-responsive structural build-up of cementitious pastes with and without PCE, it is revealed that the application of an external magnetic field to a highly flowable cementitious paste with PCE mainly plays a significant role in the increase of solid-like properties.